(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the role of literature in the process of constructing and reconstructing national identity. Special attention is paid to the mechanisms by which modern writers turn to cultural memory to create multifaceted and dynamic images of the nation. The author analyzes how literary texts reflect and shape public consciousness, as well as how they can serve as a tool for critical reflection on historical experience.